Cognitive Metaphors Expressed through Color Names in the Poems of Bavuudorj Ts. - Shoovdor, Gantulga (Mongolian Language and Literature Studies, 2025)
This article explores the use of color imagery and its cognitive-metaphorical characteristics in the poetry of the Mongolian poet Ts. Bavuudorj. The purpose of the study is to examine how color expressions penetrate the human inner world, existential philosophy, and cultural consciousness within the framework of cognitive metaphor theory. Observation, sampling, semantic, and stylistic analysis methods were applied, and a total of fourteen color terms with 229 occurrences were identified. The findings reveal that color expressions go beyond aesthetic ornamentation and embody profound meanings related to emotion, existence, and cultural awareness. The color white represents purity, spirituality, aging, and transience; blue symbolizes celestial vastness and tranquility; golden evokes nostalgia and serenity; and variegated (multicolored) signifies the harmony of opposites. Thus, in Bavuudorj’s poetry, color functions not merely as a visual element but as a cognitive-metaphorical system that expresses the interrelation between human beings and nature, space and time, reflecting the unique worldview and cultural cognition of the Mongolian people. Ц.Бавуудоржийн яруу найраг дахь өнгөний нэрээр илрэх танин мэдэхүйн зүйрлэл Хураангуй: Энэхүү өгүүлэлд яруу найрагч Ц.Бавуудоржийн уран бүтээл дэх өнгөний илэрхийлэл, түүний танин мэдэхүйн зүйрлэлийн онцлогийг судлав. Өнгөний илэрхийлэл хүний дотоод ертөнц, оршихуйн философи, соёлын ухамсарт хэрхэн нэвтэрч буйг танин мэдэхүйн зүйрлэлийн онолын хүрээнд тодруулахад уг судалгааны зорилго оршино. Судалгаанд нийт 14 өнгөний нэр, 229 удаагийн давтамжийг түүвэрлэн үндсэн хэрэглэгдэхүүн болгов. Судалгааны үр дүнгээс харахад өнгө нь яруу найргийн гоо зүйн үүргээс давж, хүний сэтгэл, оршихуй, соёлын ухамсрын гүн утгыг илтгэж байна. Цагаан өнгө нь ариун, гэгээн чанар, насжилт ба үгүйрлийг; хөх өнгө нь тэнгэрлэг уужим оршихуйг; шаргал өнгө нь дурсамж ба тайван байдлыг; алаг өнгө нь эсрэг тэсрэгийн зохирлыг илэрхийлжээ. Ийнхүү Ц.Бавуудоржийн уран бүтээлд өнгө нь зөвхөн дүрслэлийн хэрэгсэл бус, хүн ба байгаль, орон зай ба цаг хугацааны уялдааг илтгэсэн танин мэдэхүйн зүйрлэлийн тогтолцоо бөгөөд монгол хүний соёл, сэтгэлгээний өвөрмөц хэв шинжийг тусгасан байна. Түлхүүр үгс: Ц.Бавуудорж, уран сайхны эх, өнгө, танин мэдэхүйн хэл шинжлэл, зүйрлэл